Normal and integrable parabolic metric (φ, ξ, η, g, λ)-structures on hypersurfaces of parabolic integrable (F , G)-manifolds - Baškienė, Angelė (Lietuvos matematikos rinkinys, 2004)
Parabolic (φ, ξ, η, λ)-structures and parabolic metric  (φ, ξ, η, g, λ)-structures on hypersurfaces of parabolic integrable F-manifolds and parabolic integrable (F, G)-manifolds, respectively, are regarded. Necessary and sufficient normality and integrability conditions of these structures have been found.
Keywords: parabolic φ, ξ, η, λ-structure; parabolic metric φ, ξ, η, g, λ-structure; normality; integrability